Predictors variables of anxiety in the Spanish master athletes - Antonio Zarauz Sancho; Francisco Ruiz Juan (FEADEF, 2013)
In recent years Spain has seen a very significant increase in adults over 35 who often train and compete at all levels in athletics tracks. They are master athletes and, above them, there is no nationwide study and very few internationally there. Therefore, the objective of this research is on the one hand, know their training habits, athletic history and their anxiety level, analyzing gender differences, and secondly, obtain predictive models of anxiety based on their training habits and athletic history. We start from the assumption that, in the Spanish veteran athletes, in both sexes, there should be a moderate pre-competitive anxiety (cognitive and somatic) and high self-confidence, and anxiety will be predict by a high score in the other state of anxiety, by scoring low in self-confidence as well as to train fewer days a week and take less years training, for the highest level of competition in which they participates and not having support from a coach. By contrast, self-confidence can be predicted by low rate in the two states of anxiety, by training more days a week and have more years training, by the lower level of the competition in which it participates and for having supported a coach. The results confirmed the hypothesis regarding levels of anxiety and self-confidence but, however, unexpected results were obtained regarding the prediction thereof which are discussed later